Study of Delirium on Psychiatric Referrals at Helping Hands Community Hospital, Kathmandu, Nepal - Bhattarai, Praveen; Joshi, Devavrat (Janaki Medical College Journal of Medical Science, 2018)
Background and Objectives: Delirium is one of the most important neuro-psychiatric disorders in Consultation liaison psychiatry. There is a dearth of studies in this subject in Nepalese context. The objective of this study was to find out the demographic profile, source of referral, reason for referral and possible risk factors for delirium and association between risk factors and subtypes of delirium. Material and Methods: This is a descriptive cross-sectional study carried out in a tertiary care center over a period of six months. Delirium was diagnosed by psychiatrist based on International Classification of Disease, 10th revision, Diagnostic Criteria for Research (ICD-10 DCR) and was classified into subtypes using the Liptzin and Levkoff criteria. Data analysis was done using SPSS version 16 and chi- square test was applied to find the association between risk factors and subtypes of delirium. Results: A total of 52 cases of delirium were included in the study. Majority of cases were aged 65 years and above with male preponderance. The most common cause for referral was disturbed behavior and disorientation. Hyperactive delirium was the most common subtype of delirium. Most of the referred cases of delirium were from Medical ward and Intensive Care Unit/Critical Care Unit (ICU/CCU). Infection / Inflammation, Drug/alcohol intoxication or withdrawal and those with multiple etiologies were the most common possible causes of delirium. There was no significant difference in terms of associated risk factors between the clinical subtype (p = 0.8023). Conclusion: The presence of delirium warrants prompt intervention to identify and treat the underlying causes and consultation liaison psychiatric services should be enhanced to achieve this goal. Janaki Medical College Journal of Medical Sciences (2017) Vol. 5(2): 19-26